Novel Linezolid like Analogues: Synthesis, Characterization and Biological Evaluation: Synthesis, characterization and study of some 1, 3-oxazolone-5-one, linezolid - Vikas Gopalrao Rajurkar; Amol Radhakishan Pund (Iranian Journal of Pharmaceutical Sciences, 2014)
The synthesis of 4-(substituted benzylidene)-2-(pyrazin-2-yl) oxazol-5(4H)-one was achieved in two steps, In first step, pyrazine-2-carboxamide dissolved in EtOH, 10% KOH solution with ClCH2COOH produced compound 2-(pyrazine-2-carboxamido) acetic acid (II) and in second step, compound (II) in (CH3CO)2O with aromatic aldehyde, and catalyst potassium acetate produced title compounds 4-(substituted benzylidene)-2-(pyrazin-2-yl) oxazol-5(4H)-one (PA1-PA14). All the newly synthesized compounds structure were elucidated using various spectral techniques viz. FT-IR, 1H-NMR, GC-MS spectroscopy, and CHN elemental analysis data and screened for in vitro antimicrobial and antifungal activity. In vitro anti bacterial activity was carried out against organisms E.coli, K.pneumonia, S.aureus, and B. Subtilis as well as antifungal activity were carried out against A.niger and S. cerevisiae activity by minimum inhibitory concentration method. The most promising broad spectrum compounds PA3, PA4, and PA5 were observed and study data reveals that additions of different functional groups had varying effects on activity. In addition, the greater biological activities were observed when the electron-withdrawing groups like fluorine, bromine and chlorine were incorporated at p-position of the phenyl ring.